If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying t(7t + -1) = 0 Reorder the terms: t(-1 + 7t) = 0 (-1 * t + 7t * t) = 0 (-1t + 7t2) = 0 Solving -1t + 7t2 = 0 Solving for variable 't'. Factor out the Greatest Common Factor (GCF), 't'. t(-1 + 7t) = 0Subproblem 1
Set the factor 't' equal to zero and attempt to solve: Simplifying t = 0 Solving t = 0 Move all terms containing t to the left, all other terms to the right. Simplifying t = 0Subproblem 2
Set the factor '(-1 + 7t)' equal to zero and attempt to solve: Simplifying -1 + 7t = 0 Solving -1 + 7t = 0 Move all terms containing t to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + 7t = 0 + 1 Combine like terms: -1 + 1 = 0 0 + 7t = 0 + 1 7t = 0 + 1 Combine like terms: 0 + 1 = 1 7t = 1 Divide each side by '7'. t = 0.1428571429 Simplifying t = 0.1428571429Solution
t = {0, 0.1428571429}
| r^2+8r-58=7 | | x^2-10x-140=0 | | 2.5y=-17.5 | | 4x+3(x-1)=9x-7 | | 5(t-9)=85 | | 2.5x=4.7x+7.7 | | y=8x^2-49x+6 | | -36+20=-5x+13x | | -2+x=4 | | 6r^2-20r-16=0 | | 6abc^2-15a^2bc+6ab^2c= | | -(2x+4)=2x+3-4x+1 | | Cosx+cos(2x)+cos(3x)+cos(4x)=0 | | .5+.3y=.7y-.3 | | 25-81x^2=0 | | -7-6x=-11-7x | | 4z-21=47 | | 2.5=4.7+7.7 | | C^2+3x-7=0 | | 5z-15=-11+z | | 12-5x=-7x+12 | | x+142/9=71/3 | | 3x^2+10x=-67 | | 4c^2+8x=45 | | 6y-3y+4=-11 | | 4t^2u^2+7tu^2v+3tuw= | | 6a-5ab-9-3ab+2a= | | 10=-8+n-8 | | 5+8x=1+6x | | 12-5x=-7+12 | | -36+20=-5+13x | | 5x-16=38+2x |